2013
DOI: 10.1101/gr.153031.112
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis reveals concurrent RNA–protein interactions and identifies new RNA-binding proteins in Saccharomyces cerevisiae

Abstract: A growing body of evidence supports the existence of an extensive network of RNA-binding proteins (RBPs) whose combinatorial binding affects the post-transcriptional fate of every mRNA in the cell-yet we still do not have a complete understanding of which proteins bind to mRNA, which of these bind concurrently, and when and where in the cell they bind. We describe here a method to identify the proteins that bind to RNA concurrently with an RBP of interest, using quantitative mass spectrometry combined with RNa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 68 publications
3
66
0
Order By: Relevance
“…Notably, ZC3H14 colocalizes with nuclear speckles that contain the splicing factor SC-35 (48,52,53), suggesting a potential role for ZC3H14 in processing events such as splicing. In support of a link between Nab2/ZC3H14 and splicing, a recent proteomic study found that Nab2 associates with several splicing factors in an RNA-dependent manner (54).…”
mentioning
confidence: 98%
“…Notably, ZC3H14 colocalizes with nuclear speckles that contain the splicing factor SC-35 (48,52,53), suggesting a potential role for ZC3H14 in processing events such as splicing. In support of a link between Nab2/ZC3H14 and splicing, a recent proteomic study found that Nab2 associates with several splicing factors in an RNA-dependent manner (54).…”
mentioning
confidence: 98%
“…With such large numbers of RPBs, each of which binds multiple mRNA and/or ncRNA targets, another difficult task will be to identify which combinations of RBPs determine specific post-transcriptional fates of individual mRNAs and ncRNAs. Progress in this direction was demonstrated in a quantitative proteomic analysis in S. cerevisiae, which identified sets of RBPs that bind simultaneously to common RNA targets [50]. Computational tools for constructing and interrogating RNA-protein interaction networks and for integrating RPIs into existing gene and protein interaction networks will be needed.…”
Section: Future Directionsmentioning
confidence: 99%
“…The dual fluorescence RNA-binding assay described here can be used to validate the in vivo RNA-binding activity of candidate RBPs identified by system-wide approaches (Scherrer et al 2010;Tsvetanova et al 2010;Baltz et al 2012;Castello et al 2012;Klass et al 2013;Kwon et al 2013;Mitchell et al 2013). We assessed the RNA-binding activity of three previously known RBPs (MOV10, hnRNPC, and cytoplasmic poly(A)-binding protein [PABP]), three recently discovered RBPs (FAM98A, FAM32A, and enolase 1 [ENO1]), and three negative controls (H2B, β-actin [ACTB], eGFP).…”
Section: Validation Of Candidate Rna-binding Proteinsmentioning
confidence: 99%
“…The complexity of protein-RNA networks and their regulation substantially increased by the recent discovery of hundreds of previously unidentified noncanonical RBPs using high-content approaches (Scherrer et al 2010;Tsvetanova et al 2010;Baltz et al 2012;Castello et al 2012;Klass et al 2013;Kwon et al 2013;Mitchell et al 2013).…”
Section: Introductionmentioning
confidence: 99%